SISTEM INFORMASI PERPUSTAKAAN KANTOR REGIONAL (KANREG) 1 BKN YOGYAKARTA LIBRARY INFORMATION SYSTEM OF REGIONAL OFFICE 1 BKN YOGYAKARTA - , KINANTHI TYAS SUMINAR ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Form of improved quality and visitor services Regional Office (Kanreg) 1 BKN Yogyakata is one of the library. In Yogyakarta Kanreg 1 BKN library provides a variety of books and bulletins that can be read or borrowed by visitors. However, the library management is still done manually, so frequently encountered problems in data retrieval and data processing. Therefore, it is needed a Library Information System of Regional Office (Kanreg) 1 BKN Yogyakarta which will assist visitors in data search and management books and bulletins. Library information system is expected to facilitate visitors in search of the data book and bulletin which desirable in the library Kanreg 1 BKN Yogyakarta. In addition, this system also comes with a printed book report loan data. Library information systems of Regional Office (Kanreg) 1 BKN Yogyakarta was built using PHP programming language supported by CodeIgniter framework, jQuery, and MySQL to manage the database.